MEDIA E-BOOKLET 1000 HARI PERTAMA KEHIDUPAN TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP KADER POSYANDU - Fitria Rimadina; Dhimas Herdhianta (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2023)
Background: The First 1000 Days of Life is a critical period that begins in the womb until the age of 2 years. The 1000 HPK program can reduce the incidence of stunting which currently reaches a prevalence rate of 21.6%. SSGI 2022 data, West Java has a proportion of 20.2% of stunted children. Bandung Regency has a proportion of 25.0% stunting and Banjarsari Village as many as 220 children are indicated to be stunted. Method: This study used a Quasi-Experimental design with One-Group Pretest-Posttest Design. The study population was 60 health cadres with a sample of 38 cadres. Purposive sampling technique. Analysis of Paired T-test test data to prove the research hypothesis. Result: : The average knowledge score of cadres before being given E-Booklet 1000 HPK media was 61.21 and the average knowledge score after being given E-Booklet 1000 HPK media was 80.55. The percentage of knowledge increase was 31.59%. The p value of cadres' knowledge before and after being given the 1000 HPK E-Booklet media is (p = 0.000). Meanwhile, the percentage of cadres' attitudes before being given E-Booklet media was 47.4%. The percentage of cadres' attitudes after being given E-Booklet media was 57.9% with an increase percentage of 10.5%. The p value of cadres' knowledge before and after being given the 1000 HPK E-Booklet media is (p = 0.000). Conclusion : The influence of the 1000 HPK E-Booklet media on the Knowledge and Attitudes of Cadres as an effort to prevent stunting in Banjarsari Village, Pangalengan District. Keywords: 1000 HPK E-Booklet; Knowledge; Attitude; Cadre; Stunting